Greater loss of object than spatial mnemonic discrimination in aged adults. Issue 4 (18th January 2016) - Reagh, Zachariah M.; Ho, Huy D.; Leal, Stephanie L.; Noche, Jessica A.; Chun, Amanda; Murray, Elizabeth A.; Yassa, Michael A.
ABSTRACT: Previous studies across species have established that the aging process adversely affects certain memory‐related brain regions earlier than others. Behavioral tasks targeted at the function of vulnerable regions can provide noninvasive methods for assessing the integrity of particular components of memory throughout the lifespan. The present study modified a previous task designed to separately but concurrently test detailed memory for object identity and spatial location. Memory for objects or items is thought to rely on perirhinal and lateral entorhinal cortices, among the first targets of Alzheimer's related neurodegeneration. In line with prior work, we split an aged adult sample into "impaired" and "unimpaired" groups on the basis of a standardized word‐learning task. The "impaired" group showed widespread difficulty with memory discrimination, whereas the "unimpaired" group showed difficulty with object, but not spatial memory discrimination. These findings support the hypothesized greater age‐related impacts on memory for objects or items in older adults, perhaps even with healthy aging. © 2015 Wiley Periodicals, Inc.